Hubungan Antara Indeks Massa Tubuh Dan Nilai Volume Ekspirasi Paksa Detik 1 (Vep1) / Kapasitas Vital Paksa (Kvp) Pada Pasien Ppok Stabil Derajat Iii Di Balai Besar Kesehatan Paru Masyarakat (Bbkpm) Surakarta - PERMATASARI, REISWANDHIKA INTAN, dr. Niwan Tristanto Martika, Sp. P (2016)
The classification of chronic obstructive pulmonary disease (COPD) can be seen from the % forced ekspiratory volume in 1 second (%FEV1) or FEV1 predictions and forced ekspiratory volume in 1 second (FEV1) / forced vital capacity (FVC). Weight loss due to inadequate dietary intake correlated with poor prognosis of COPD. Body Mass Index (BMI) is the simplest way to monitor the nutritional status of a person. BMI decline will affect the muscular work of respiratory muscles, causing the value of FEV1/FVC decrease. The purpose for this study is To determine the correlations between BMI and FEV1/FVC in patients stable COPD grade III. Methods of analytic cross sectional observational study. Research conducted in February 2016 at The Center for Lung Health Community of Surakarta. The sample was taken by purposive sampling technique. Data analysis using SPSS 17.0 program with Spearman Correlations test. The Results is the majority of BMI in this study is 18.85 and FEV1/FVC is 60.77 The statistical analysis showed the p value = -0.195 With spearman correlations = 0.373. the Conclusion is there is no significant correlations between BMI and FEV1/FVC in patients with stable COPD grade III at the The Center for Lung Health Community of Surakarta. Keywords : Stable COPD Grade III, BMI, FEV1/FVC